Pemberitaan Peluncuran Bank Emas Pertama Dan Kebijakan Tarif Trump 2.0 Terhadap Daya Investasi Masyarakat - Pramelani, Pramelani; Muhariani, Wulan (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The rise of negative news in investing in the media is one of the steps taken by the public to have an interest in saving. The influence of the media in the search for information carried out by the public also determines the behavior they do. News of the launch of the first gold bank or bullion bank launched by the president is an opportunity for the public to vary in investing. In addition, the emergence of news in the media regarding the Trump 2.0 tariff policy several months after the launch of the gold bank in Indonesia. With the news in the media, how is the public's investment power in gold products. The research method used is a qualitative descriptive method with interview techniques to informants spread across residential areas of DKI Jakarta and also in-depth data regarding news in the media which is then analyzed. The results of the study found that the public's investment power was very high in gold products when media coverage highlighted the Trump 2.0 tariff policy which was feared to have an impact on the Indonesian economy. The media coverage had an extraordinary media effect so that it changed people's behavior into panic buying. This media effect is different from the initial launch of the first gold bank in Indonesia which had not changed public awareness of the power of gold investment before the news of the Trump 2.0 tariff policy.